Long term adherence to dietary recommendations after inpatient rehabilitation: prospective follow up study of patients with coronary heart disease. Issue 5 (13th September 2005) - Twardella, D; Merx, H; Hahmann, H; Wüsten, B; Rothenbacher, D; Brenner, H
Abstract : Objective: To evaluate the adherence to nutritional recommendations in inpatient rehabilitation and the long term maintenance of dietary changes among patients with coronary heart disease. Design: Prospective cohort study. Setting: Two rehabilitation clinics in Germany. Participants: A cohort of 1206 patients undergoing inpatient rehabilitation after an acute manifestation of coronary heart disease. Main outcome measures: Self reported dietary intake before, during, and one and three years after rehabilitation measured with a semiquantitative food frequency questionnaire and summarised to a nutritional index, which was used to categorise patients as having a poor, fair, or good diet. Results: During rehabilitation the proportion of patients whose dietary intake was categorised as good increased strongly from 30% to 91%. One and three years after rehabilitation a still increased proportion of 49% and 42%, respectively, in the good category was observed. The strong increase in intake of low fat and wholemeal products that was achieved during rehabilitation was followed after rehabilitation discharge by a backslide to the intake observed before rehabilitation admission. The avoidance of unfavourable food items, such as French fries or eggs, was at least partly maintained during the follow up period. Conclusion: During inpatient rehabilitation most patients do have to make major changes in their dietary intake to comply with recommendations. Although some proportion of patients continue to adhere to dietary recommendations in the long run, further research into strategies to improve maintenance of dietary changes is needed to enhance further the long term benefits from cardiac rehabilitation.